Pengaruh Belanja Pendidikan, Belanja Kesehatan dan PDRB Terhadap IPM di Propinsi-Provinsi Indonesia Tahun 2020-2024 - Fernando, Billy; Yustie, Renta (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Human development in Indonesia exhibits significant disparities between regions despite a national increase in the Human Development Index (HDI). This fact indicates the uneven quality of basic services and challenges regarding the effectiveness of local government spending allocation, especially in the education and health sectors. This research aims to analyze the partial and simultaneous influence of Education Spending, Health Spending, and Regional Gross Domestic Product (RGDP) on the HDI. A quantitative method using panel data from 34 Indonesian provinces covering the 2020 to 2024 period was applied. The panel data regression model was utilized to test the causal relationship between the variables after conducting the Chow and Hausman tests. The estimation results indicate that Education Spending has a negative and significant effect on the HDI. This finding is interpreted as inefficiency in the allocation of the education budget, which tends to be absorbed more by routine and administrative expenditures than by direct investment in improving the quality of the learning process. Health Spending was proven to have no significant influence, suggesting governance issues in the implementation of local health programs. Meanwhile, the Regional Gross Domestic Product (RGDP) was found to have a positive and significant effect on the HDI. Simultaneously, all three variables provide a significant contribution to the HDI. Based on these findings, a reformulation of local fiscal policy is required so that the allocation of Education Spending is oriented toward quality improvement, rather than merely increasing budget quantity, along with improving the effectiveness of health spending.